Strong support for BN: Telling details: UUM poll shows 58pc of electorate backing Najib - Fernandez, Elvina (New Straits Times, 2013)
BARISAN Nasional will receive strong support from voters in the upcoming general flection, according to a survey by Universiti Utara Malaysia's Malaysian Political Research Institute and the National Council of Professors (MPN).